Profile Study of a School Going Child with Haemophilia - Singh, Vinay Kumar (INDIAN EDUCATIONAL REVIEW, 2020)
The Rights of Persons with Disabilities Act, 2016 has specified 21 disabilities in its schedule where haemophilia has been added as one of the disability. Haemophilia is a bleeding disorder. A profile study of a school going child with haemophilia was conducted to identify the difficulties faced by the child in learning as well as carrying out day-to-day activities. A qualitative single case research design was adopted. Self designed research tools were administered to collect information. The findings revealed that there was very low or no awareness among stakeholders regarding haemophilia, its causes, symptoms, diagnosis, treatment and overall management. The child was facing lot of difficulties in learning due to his persistence absences from school and restricted participation in school activities because of his inconsistent episodes of internal or external bleeding, injuries and consecutive treatment. The school did not have any guidelines, specific educational intervention as well as individualised support programme for taking care of his health emergency, safety, education and coping with stress and pain. Teachers and parents, both, expressed their needs for training and support with regard to education and management of children with haemophilia